2013
DOI: 10.1164/rccm.201205-0875oc
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Elastase Degrades Cystic Fibrosis Transmembrane Conductance Regulator via Calpains and Disables Channel FunctionIn VitroandIn Vivo

Abstract: These data provide a new mechanism and show for the first time a link between NE-calpains activation and CFTR loss of function in bacterial lung infections relevant to CF and to other chronic inflammatory lung conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 48 publications
3
67
0
1
Order By: Relevance
“…Importantly, we validated these data in vivo, by showing : a) that the intranasal instillation of NE in WT C57/Bl6 mice inactivated CFTR structure and Cl -channel function, and b) that P.a lung infection also led to WT-CFTR inactivation, the latter being partly dependent on host NE activity (34). Indeed, following P.a lung infection, NE KO mice were still sensitive (albeit less than WT) to P.a-mediated CFTR degradation, compared to WT mice.…”
Section: Impaired Mucosal Innate Immune Response In Cf: a Role For Prsupporting
confidence: 58%
See 2 more Smart Citations
“…Importantly, we validated these data in vivo, by showing : a) that the intranasal instillation of NE in WT C57/Bl6 mice inactivated CFTR structure and Cl -channel function, and b) that P.a lung infection also led to WT-CFTR inactivation, the latter being partly dependent on host NE activity (34). Indeed, following P.a lung infection, NE KO mice were still sensitive (albeit less than WT) to P.a-mediated CFTR degradation, compared to WT mice.…”
Section: Impaired Mucosal Innate Immune Response In Cf: a Role For Prsupporting
confidence: 58%
“…Mechanistically, we also demonstrated that NE cleaved CFTR through the activation of intracellular calpains (34).…”
Section: Impaired Mucosal Innate Immune Response In Cf: a Role For Prmentioning
confidence: 56%
See 1 more Smart Citation
“…Furthermore, recent studies demonstrated that NE leads to degradation and loss of CFTR Cl -channel function through a pathway involving the activation of intracellular calpains ( fig. 1) [47]. Therefore, an imbalance between NE and potentially other proteases released from inflammatory cells or bacteria on the one hand, and protective anti-proteases on the other hand [44], may inevitably aggravate airway surface dehydration and also impede therapeutic approaches targeting the basic ion transport defect in CF airways once chronic inflammation and infection are established.…”
Section: Airway Proteases Aggravate Basic Cf Ion Transport Defectmentioning
confidence: 99%
“…However, the consequences of exposure to infections on CFTR channel expression and function have not been clearly defined. In fact, contradictory results have been reported depending on the bacterial strain, the duration of exposure to infection, as well as the cellular models tested [6][7][8][9]. However, it is crucial to understand the outcomes of microbial infection on CFTR.…”
Section: Introductionmentioning
confidence: 99%